Genotyping of CARD15/NOD2, ATG16L1 and IL23R Genes in Polish Crohn’s Disease (CD) Patients – Are They Related to the Localization of the Disease and Extra-Intestinal Symptoms? - Jakubowska-Burek, Ludwika; Kaczmarek, Elzbieta; Hoppe-Golebiewska, Justyna; Kaczmarek-Rys, Marta; Hryhorowicz, Szymon; Kucharski, Marcin A.; Slomski, Ryszard; Linke, Krzysztof; Dobrowolska-Zachwieja, Agnieszka (IntechOpen, 2012)
None